2020
DOI: 10.1161/atvbaha.120.314860
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Thrombosis in Patients With COVID-19—Brief Report

Abstract: Objective: Alveolar-capillary endothelial cells can be activated by severe acute respiratory syndrome coronavirus 2 infection leading to cytokine release. This could trigger endothelial dysfunction, pyroptosis, and thrombosis, which are the vascular changes, commonly referred to as coronavirus disease 2019 (COVID-19) endotheliopathy. Thus, this study aimed to identify tissue biomarkers associated with endothelial activation/dysfunction and the pyroptosis pathway in the lung samples of patients with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
146
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 5 publications
2
146
1
6
Order By: Relevance
“…10 It has been suggested that the virus instigates the process of pyroptosis , an inflammatory form of programmed cell death observed upon infection with intracellular pathogens, which could contribute to the endothelial cell death after COVID-19 infection and could increase proinflammatory cytokine releases, such as interleukin (IL)-1 beta and IL-18. 11 Both these pathologic processes of endothelial dysfunction and pyroptosis might lead to systemic thrombotic events. 11 Monitoring of coagulation indices in severely ill COVID-19 patients seems imperative to identify those patients at increased thromboembolic risk and to adjust thromboprophylaxis accordingly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It has been suggested that the virus instigates the process of pyroptosis , an inflammatory form of programmed cell death observed upon infection with intracellular pathogens, which could contribute to the endothelial cell death after COVID-19 infection and could increase proinflammatory cytokine releases, such as interleukin (IL)-1 beta and IL-18. 11 Both these pathologic processes of endothelial dysfunction and pyroptosis might lead to systemic thrombotic events. 11 Monitoring of coagulation indices in severely ill COVID-19 patients seems imperative to identify those patients at increased thromboembolic risk and to adjust thromboprophylaxis accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…11 Both these pathologic processes of endothelial dysfunction and pyroptosis might lead to systemic thrombotic events. 11 Monitoring of coagulation indices in severely ill COVID-19 patients seems imperative to identify those patients at increased thromboembolic risk and to adjust thromboprophylaxis accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction induces inflammation and vascular remodeling ( 38 ), which are associated with severe COVID-19. Endotheliopathy or endothelial dysfunction, including endothelial activation, endotheliitis, and thrombotic events, is an indicator of coagulopathy in COVID-19 patients ( 33 , 34 , 39 ).…”
Section: New Mechanisms Underlying Thrombosis and Coagulopathy In Covmentioning
confidence: 99%
“…Upregulation of vascular endothelial growth factor and downregulation of E-cadherin expression enhance the permeability of endothelial cells in COVID-19 patients ( 41 ). In addition, biopsy of lung tissues of COVID-19 patients shows upregulation of interleukin-6 (IL-6), tumor necrosis factor-α, intercellular adhesion molecule-1, and caspase-1 expression ( 39 ). Further, quantitative analysis showed a significant increase in expression levels of von Willebrand factor antigen and soluble P-selectin, which are markers of endothelial cell and platelet activation, in COVID-19 patients admitted to intensive care units ( 34 ).…”
Section: New Mechanisms Underlying Thrombosis and Coagulopathy In Covmentioning
confidence: 99%
“…При иммуногистохимическом исследовании посмертных препаратов легких пациентов, умерших от SARS-CoV-2-инфекции, было выявлено повышение экспрессии маркеров эндотелиальной дисфункциимолекулы межклеточной адгезии 1-го типа (ICAM-1) и каспазы-1. Авторы [41] связывают экспрессию молекулы ICAM-1 с формированием стойкого эндотелиита. Активация каспазы-1 с высвобождением провоспалительных цитокинов играет важную роль в механизмах развития пироптоза, который ведет к фрагментации эндотелиоцитов и их гибели.…”
Section: изменения в системе гемостаза при Sars-cov-2-инфекцииunclassified